Influência do TCSC na energia transitória dos sistemas de potência - Colvara, Laurence Duarte (Institute of Electrical and Electronics Engineers (IEEE), 2005)
The problem of power system stability including the effects of Flexible Alternating Current Transmission System (FACTS) is approached. The Controlled Series Compensator is considered, and its effects upon synchronizing and damping torque are analyzed by means of the properties of the potential part of the transient energy as well as the ones of the Lyapunov Function time derivative. First, the single-machine infinite bus system is approached in details and then the results are generalized to the multimachine power system both of them expressed with nonlinear nature preservation.
The influence of the TCSC on power system transient energy
Keywords: Direct methods; Energy function; FACTS; Power system stability; TCSC